2017
DOI: 10.1002/cmdc.201700340
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potent Phosphoinositide 3‐Kinase Pan Inhibitor Displaying a Strategic Carboxylic Acid Group and Development of Its Prodrugs

Abstract: Activation of the phosphoinositide 3‐kinase (PI3K) pathway is a key signaling event in cancer, inflammation, and other proliferative diseases. PI3K inhibitors are already approved for some specific clinical indications, but their systemic on‐target toxicity limits their larger use. In particular, whereas toxicity is tolerable in acute treatment of life‐threatening diseases, this is less acceptable in chronic conditions. In the past, the strategy to overcome this drawback was to block selected isoforms mainly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Peak plasma concentration 5 min after i.v. administration showed that CL27e was twice more abundant than CL27c (Supplementary Table 3 ), as previously shown 14 . After i.v.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Peak plasma concentration 5 min after i.v. administration showed that CL27e was twice more abundant than CL27c (Supplementary Table 3 ), as previously shown 14 . After i.v.…”
Section: Resultssupporting
confidence: 85%
“…To circumvent this drawback, CL27c (Supplementary Fig. 1a ) (Patent: WO/2012/073184) was designed as a cell-permeable lipophilic ester prodrug 14 . This compound is inactive in PI3K enzymatic assay with purified proteins but, once inside the cytoplasm, is metabolized by unspecific esterases into CL27e (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several PI3K inhibitors are currently being evaluated in clinical trials. Pan‐Class I‐PI3K inhibitors, which act by targeting all 4 class I PI3K isoforms, have shown modest clinical efficacy in clinical trials . The toxicities associated with pan‐PI3K inhibitors, such as buparlisib (BELLE‐2 and BELLE‐3 trials) and pictilisib (FERGI trial), limit the clinical utility of these agents.…”
Section: Introductionmentioning
confidence: 99%